How to ensure nutrition for everyone under climate change and variability - Fanzo, Jessica; McLaren, Rebecca; Davis, Claire; Choufani, Jowel (International Food Policy Research Institute, 2017)
This policy note summarizes research presented in an International Food Policy Research Institute discussion paper (Fanzo et al. 2017b) that utilizes a food systems approach to analyze the multifaceted interrelationships among climate change, food, and nutrition along the entire food value chain.